An Ottoman Armenian orphanage :|the short history of Dârüleytâm-ı Osmânî in Adana (1909-1918) - Akpınar, Uğur. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2020., 2020)
This thesis examines the history of Dârüleytâm-ı Osmânî institution founded in Adana by Adana Governor Cemal Pasha of the period for Armenian girls and boys who were orphaned due to the Adana massacres of 1909. This orphanage, whose foundations were laid in 1909, was officially opened in 1911 for the education and care of 500 hundred orphaned Armenian children. Shortly after its opening, Muslim orphans were also placed in the orphanage and thus became a multireligious and multicultural institution. This thesis tries to show the views of local officials, Ottoman Armenians, and the Committee of Union and Progress towards the opening of the orphanage, by emphasizing the historical role of the Armenian orphans. While drawing a comprehensive picture of the process providing the establishment of the orphanage from 1909 to 1911, this thesis argues that this orphanage was founded for political reasons rather than humanitarian concerns. The study shows the partnerships, disputes, and conflicts between different groups through the discussions on the administration and control of the orphanage from 1912 to 1914. Furthermore, the thesis shows the impacts of the changing ideological, social, and economic policies of the government on the orphanage by focusing on the period between 1914 and 1918. The primary sources used in this thesis are Ottoman archival documents, missionary and consul reports, memoirs, newspapers, province budgets, and regulations.
Keywords: Orphanages -- Turkey.; Armenians -- Turkey -- Social conditions.